Greening coil coating paint manufacturing premise using cleaner production strategies / Choo Chai Cheng - Choo, Chai Cheng (2019)
Coil coating paint manufacture premise was chosen to evaluate the opportunities for using cleaner production strategies to green the premise. This study aims to reduce the carbon dioxide emission included total resources usage and waste generation from the coil coating paint manufacturing activities. The audit result shows that the carbon emission from coil coating paint is 166.0 kg CO2 / 1000kg of coil coating paint. To produce one kg of paint, it requires 0.19 kWh electricity, 0.8g LPG and 0.016 kg of the waste generation which include solid and liquid waste. Total of twenty-seven (27) cleaner production options were identified to reduce carbon emission. The cleaner production options mainly focus on the design changes, improvement in term of operational, and good housekeeping. The analyses show that the cleaner production options can reduce the carbon emission about 55.5 kg CO2 / 1000kg of coil coating paint. This will be a total reduction of 33.3 x 104 tonne CO2 per year for selected coil coating paint manufacture premise. The implementation of cleaner production options required approximately RM 1,000,500 investment with the payback period of about 4.4 years. Therefore, the cleaner production strategy helps to reduced carbon dioxide emission and it is a useful tool to green the coil coating paint manufacturing premise with attractive financial return.